(3HQfGeL bGFe Ydi CdYGH GdYbd GdEdcJQhfjI GdJaGYdjI dJfejI egGQGJ GdJYde GdOeGZi dWad GdQhVI (B/ s - (3SGQI QeRi EHQGgje SdjeGfs; (3EHJgGL eMehO WdHg (B: s; (3TjeGA eMeO Ydi TfOi (B: s ((3GdbGgQI (B: s (3SGQI QeRi EHQGgje SdjeGf (B: s, 2020)
(3jgOa GdHMK Edi JfejI egGQGJ GdJYde GdOeGZi dOi Wad GdQhVI ef NdGd HQfGeL bGFe Ydi CdYGH GdYbd GdEdcJQhfjI GdJaGYdjI(B: (3h JchfJ YjfI GdHMK ef (B30 (3Wad h WadI ef CWaGd GdeSJhi GdKGfi QjGV GdCWaGd(B: (3h GSJNOeJ GdOQGSI GdCOhGJ GdBJjI(B: (3ebjGS dJfejI egGQGJ GdJYde GdOeGZi dWad GdQhVI(B. ((3EYOGO GdHGMKI(B). (3HQfGeL bGFe CdYGH GdYbd GdEdcJQhfjI GdJaGYdjI dJfejI egGQGJ GdJYde GdOeGZi dOi Wad GdQhVI(B. ((3EYOGO GdHGMKI(B). (3h CSaQJ fJGFL GdOQGSI Yf(B: (3YOe hLhO aQhb PGJ OdGdI EMUGFjI Hjf eJhSW OQLGJ CWaGd GdeLehYI GdVGHWI Hjf GdbjGSjf GdbHdi h GdHYOi Ydi ebjGS egGQGJ GdJYde GdOeGZi(B. (3hLhO aQhb PGJ OdGdI EMUGFjI YfO eSJhi (B0.01 (3Hjf eJhSW OQLGJ CWaGd GdeLehYI GdJLQjHjI Hjf GdbjGSjf GdbHdi h GdHYOi dJWHjb HQfGeL bGFe Ydi CdYGH GdYbd GdEdcJQhfjI GdJaGYdjI dJfejI egGQGJ GdJYde GdOeGZi dWad GdQhVI Ydi ebjGS egGQGJ GdJYde GdOeGZi dUGdM GdbjGS GdHYOi(B. (3hLhO aQhb PGJ OdGdI EMUGFjI YfO eSJhi (B0.01 (3Hjf eJhSWGJ OQLGJ GdeLehYI GdJLQjHjI h eJhSWGJ OQLGJ GdeLehYI GdVGHWI HYO JWHjb HQfGeL bGFe Ydi CdYGH GdYbd GdEdcJQhfjI GdJaGYdjI dJfejI egGQGJ GdJYde GdOeGZi Ydi ebjGS egGQGJ GdJYde GdOeGZi dUGdM GdeLehYI GdJLQjHjI(B. (3fSHI GdcSH deJhSWGJ OQLGJ CWaGd GdeLehYI GdJLQjHjI Ydi ebjGS egGQGJ GdJYde GdOeGZi CYdi ef fSHI GdcSH deJhSWGJ OQLGJ GdeLehYI GdVGHWI HYO JWHjb HQfGeL bGFe Ydi CdYGH GdYbd GdEdcJQhfjI GdJaGYdjI dJfejI egGQGJ GdJYde GdOeGZi(B. (3YOe hLhO aQhb PGJ OdGdI EMUGFjI Hjf eJhSW OQLGJ CWaGd GdeLehYI GdJLQjHjI Hjf GdbjGSjf GdHYOi h GdJJHYi dJWHjb GdHQfGeL GdbGFe Ydi CdYGH GdYbd GdEdcJQhfjI GdJaGYdjI dJfejI egGQGJ GdJYde GdOeGZi Ydi ebjGS egGQGJ GdJYde GdOeGZis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjg ddWahdI GdeHcQI (B- (3bSe GdYdhe GdJQHhjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJYde GdOeGZis; (3CdYGH GdYbd GdEdcJQhfjI GdJaGYdjIs; (3Wad GdQhVIs